The Effect of mAs Variation on Noise in Phantom Pelvis Using a Computer Radiography (CR) - Dewilza, Nerifa (PT. Hafasy Dwi Nawasena, 2026)
The quality of radiographic images is the accuracy of the patient's anatomical representation on the radiographic image. To produce high-quality images, the most important characteristics of radiographic image quality are spatial resolution, contrast resolution, noise, and artifacts. An increase in tube current causes a decrease in noise value. In radiographic imaging, noise is influenced by several factors including the strength of the tube current. Basically the tube current chosen is at the highest mAs that the aircraft can achieve, so that the exposure time can be as short as possible, so as to prevent image blurring caused by movement. This study aims to analyze the influence of mAs varieties on noise on radiographic images. This research was carried out using an experimental study method at Siti Rahma Padang Hospital, on May 27, 2024. Using the phantom pelvis of Baiturrahmah University Padang to obtain the results of the description of five different variations of mAs: mAs 8, mAs 10, mAs 12, mAs 14, mAs 16, with a tube voltage of 70. The data was processed using SPSS using the ANOVA One Way test, in the form of a table. Producing a calculated F value of 4.673 which shows a significant relationship between the strength of the tube current and noise with ap value of 0.002 (< 0.05). This study concluded that there was a significant influence between the results of mAs variation on noise.